LEXICAL AMBIGUITY ON NEWS HEADLINE OF CNN NEWS’ OFFICIAL TIKTOK ACCOUNT VIDEOS - Ni Made Ari Santhi; Ni Putu Cahyani Putri Utami (British (Jurnal Bahasa dan Sastra Inggris), 2023)
The objective of this study was to find out the types of lexical ambiguity in CNN News’ official TikTok account videos. This study applied the theory of lexical ambiguity proposed by Murphy (2010). The descriptive-qualitative research method was used to explain the final results. The data in this study were taken from headlines of TikTok videos published from May 2023 to July 2023. The data was collected by documentation and observation methods. The results of the data analysis showed that 5 headlines considered lexical ambiguity in the news video on CNN News’ official TikTok. Polysemy and homonymy were found in this study as the types of lexical ambiguity. There were 2 words and 1 phrase identified as polysemy, and 2 words identified as homonymy. The type of lexical ambiguity mostly found is polysemy.